Carbapenems: A literature Review regarding Resistance, Risk Factors, and Mortality in Pneumonia - Tania R. Amalia; Eli Halimah; Riyadi Adrizain; Miski A. Khairinisa (Pharmacology and Clinical Pharmacy Research, 2021)
Carbapenem is one of antibiotic to treat respiratory infections such as pneumonia that frequently used in tertiary care facilities and started to create resistances. This study aims to review the resistance of carbapenems, assess the risk factors for resistance that leads to mortality, and the more effective antibiotic treatment options to overcome the resistance. Assessment of the use of carbapenems in pneumonia through previous studies were carried out by searching the articles in search engine databases in 2011 to 2021. Articles reporting carbapenems resistance, risk factors, and mortality were selected based on inclusion and exclusion criteria. Of 14 articles included in inclusion criteria, 4 studies reported the occurrence of resistance to gram-negative bacteria such as Acinetobacter aumanii, Pseudomonas aeruginosa, and Klebsiella pneumoniae, and 10 articles reported risk factors and mortality. The risk factors for carbapenems resistance are the history of carbapenems use, duration of hospitalization, use of mechanical ventilation, high Simplified Acute Physiology Score (SAPS) scores, and high Acute Physiologic and Chronic Health Evaluation (APACHE). Carbapenems resistance causes mortality such as septic shock, high Sequential Organ Failure Assessment (SOFA) scores, and elevated risk at > 60 years of age, female sex, and inappropriate choice of antibiotics. The results showed that imipenem has higher resistance than other carbapenems members, the risk factors for carbapenems resistance are dominated by a history of carbapenems use, mortality caused by high score SOFA, and colistin can be the current choice to overcome carbapenems resistance.